Cheek teeth apical infection in cattle: Diagnosis, surgical extraction, and prognosis. Issue 5 (7th April 2019) - Constant, Caroline; Nichols, Sylvain; Marchionatti, Emma; Babkine, Marie; Lardé, Hélène; Fecteau, Gilles; Desrochers, André
Abstract: Objective: To report the clinical presentation, treatment, and outcome of cattle undergoing surgical extraction of apically infected cheek teeth (CT). Study design: Short case series. Animals: Nine adult cattle. Methods: Medical records were searched for cattle having a diagnosis of apical infection of CT that were treated with surgical extraction between 2005 and 2017. Data retrieved included clinical examination, ancillary tests, surgical procedure, and outcomes. Results: The main presenting complaints were mandibular swelling and decreased appetite and milk production. In total, 7 mandibular and 3 maxillary CT were extracted, 7 molars and 3 premolars that were distributed more frequently on the left dental arcades (n = 7 CT). Two cattle had no visible external lesions. Radiograph images revealed that lucency surrounded all affected tooth roots. Mandibular teeth were removed by lateral buccotomy with removal of alveolar bone plate or retrograde repulsion, and maxillary teeth were removed by repulsion through a maxillary sinus flap. Most common bacterial isolates consisted of anaerobic bacteria (6/11 isolates) and Truperella pyogenes (3/11 isolates). The most common complications included inability to remove the tooth intact (n = 4 cattle) and surgical site infection (n = 5). All cattle remained in their herd after treatment. Conclusion: Surgical extraction of CT was achieved in all 9 cattle. The postoperative morbidity was high but without long‐term consequences on animal productivity. Clinical significance: Surgical extraction of CT is a successful treatment for apical infection in cattle.